Training on making compost blocks using agroforestry waste for the Pujo Makmur forest farmers group, Pesawaran Regency, Lampung - Surnayanti Surnayanti; Machya Kartika Tsani; Sugeng Prayitno Harianto; Trio Santoso; Bainah Sari Dewi; Mirza Wistary; Mohamad Arif Prasetyo; Widya Anisa Rachmah; Danti Maharanti (Universitas Muhammadiyah Magelang, 2024)
Protected forests serve as the fundamental protection for the support system of life, regulating water resources, preventing floods, controlling erosion, mitigating saltwater intrusion, and preserving soil fertility. However, in reality, many protected forests are converted into agricultural land. To address this issue, the government grants land use permits through the Community Forest (HKm) system. The HKm system typically involves planting a combination of agricultural and forestry crops (agroforestry). The variety of crops grown in one area yields abundant harvests, but it also generates a significant amount of waste. Consequently, waste becomes a problem, although plant waste can be utilized to make compost. The objective of this community service activity is to provide education and training on making compost blocks. The method employed in this activity is education and training provided to farmers. The results of this community service activity enhance the knowledge of the Pujo Makmur Farmer Group regarding the benefits of compost blocks, the process of making them, and their usage.